2020
DOI: 10.20944/preprints202006.0303.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding Livelihood Characteristics and Vulnerabilities of Small-scale Fishers in Coastal Bangladesh

Abstract: Small-scale fishers are considered as one of the most vulnerable communities in Bangladesh but very few studies focused on the livelihood sustainability and vulnerabilities of this professional group. A fieldwork in lower Padma and upper Meghna hilsa sanctuaries identifies different livelihood characters and associated vulnerabilities of the fishers. A conceptual framework known as Sustainable Livelihood Approaches (SLA) has been introduced to analyses the qualitative and quantitative data. The insights of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…The research findings showed that most fishers had inadequate income and poor housing facilities, which is concordant with other studies' findings in Bangladesh [37,38]. Fishers were identified as having not received proper institutional education and bearing the responsibilities of large family sizes [39,40]. They, in turn, cannot afford to send their children to school, which is relevant to SDG 4 which addresses access to quality education.…”
Section: Fisher's Livelihood and Vulnerabilities: Observations From Fieldworksupporting
confidence: 81%
“…The research findings showed that most fishers had inadequate income and poor housing facilities, which is concordant with other studies' findings in Bangladesh [37,38]. Fishers were identified as having not received proper institutional education and bearing the responsibilities of large family sizes [39,40]. They, in turn, cannot afford to send their children to school, which is relevant to SDG 4 which addresses access to quality education.…”
Section: Fisher's Livelihood and Vulnerabilities: Observations From Fieldworksupporting
confidence: 81%
“…Small-scale fisheries are a sector that is heterogeneous at various levels (spatial, temporal, tool diversity), has different social and cultural importance, has its own characteristics, and is very difficult to define [26]. Small-scale fishers in Bangladesh are among the most vulnerable communities in society, living with extreme stratification, discrimination, social exclusion, and economic domination [19]. Their livelihoods and living conditions are still below average in the adjacent Padma and Meghna Rivers.…”
Section: Discussionmentioning
confidence: 99%
“…New diagnostic approaches to contextualize fisheries and seek suitable entry points are needed to transform them into social-ecological sustainability and secure future livelihoods [16][17][18]. Small-scale hilsa fishers in Bangladesh are among the most vulnerable communities in society, living with extreme stratification, discrimination, social exclusion, and economic oppression [19]. These fishers occupy a lower position in Bangladeshi society due to their weak economic capacity, limited professional skills, and living options [12].…”
Section: Introductionmentioning
confidence: 99%
“…Children living in poor sanitary conditions are more exposed to large amounts of pathogens, especially between 6 months and 2 years when they begin to crawl on the floor and throw objects into their mouths. Researchers further suggested that environmental entropy could be a significant factor in poor growth and could compromise the effectiveness of nutritional interventions ( 13 , 14 ). The relationship between diarrhea and malnutrition is complex, although it is well-known that malnourished children suffer frequent episodes of diarrhea, while a child's nutritional status is also affected after the diarrhea episode.…”
Section: Introductionmentioning
confidence: 99%